UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) SISWA KELAS III SDN 016 SEKELADI - ', Horiah; ', Zuhri D; ', Suhermi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The research was classroom action research that aims to improve mathematics learning outcomes with applied the cooperative learning type Numbered Heads Together. The subject of the research is students of class III SD Negeri 016 Sekeladi at the second semester of academic years 2014/2015. There are 24 students in the class, consist of 12 boys and 12 girls who have heterogeneous academic ability. The research are two cycles. Each a cycle has four stages, that are planning, implementation, observation, and reflection. Each end of the cycle of daily tests carried out. Data collected through observation and tests in the form of daily tests. Results of this research showed that the teacher’s activities and students have done well after doing the action. The action is successful if the number of students who achieve a score basis increase in daily tests I and II. The number of students who achieve a score of minimum mastery criteria on basic, daily test I (first cycle) and daily test II (second cycle) are respectively 16,7%, 37,5 %, and 58,3%. The result of this research shows that the type Numbered Heads Together Cooperative Learning Approaches can improve the mathematics achievement from the students of class III SD Negeri 016 Sekeladi at the second semester of academic years 2014/2015.Keywords: Mathematics learning outcome, Cooperative learning, Numbered Heads Together, Class action research